2020
DOI: 10.36740/wlek202005119
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Hypertension Associated With Hyperuricemia: Features of Heart Damage

Abstract: The aim is the analysis of hyperuricemia influence on the heart features in patients with arterial hypertension. Materials and methods: We include 75 patients with arterial hypertension which were divided in two groups according to the level of uric acid in the blood, 30 practically healthy people. Patients from the I group (n = 40) had arterial hypertension and coexistent hyperuricemia; ІІ (n = 35) – arterial hypertension. Left ventricular mass index was determined for left ventricular hypertrophy confirmatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It has been observed that both albuminuria and LVH have a higher risk of associated HU. This is important because both lesions are closely linked with HTN [33,40,41], but also in patients with metabolic disorders such as obesity and DM [42,43]. Something similar happens to those CVD cases associated with a higher risk of HU, such as AFIB and HF, both directly related to HTN [44].…”
Section: Discussionmentioning
confidence: 95%
“…It has been observed that both albuminuria and LVH have a higher risk of associated HU. This is important because both lesions are closely linked with HTN [33,40,41], but also in patients with metabolic disorders such as obesity and DM [42,43]. Something similar happens to those CVD cases associated with a higher risk of HU, such as AFIB and HF, both directly related to HTN [44].…”
Section: Discussionmentioning
confidence: 95%
“…Epidemiological and experimental evidence supports the idea that elevated serum urate concentrations contribute to gout, kidney disease, hypertension, and diabetes. [5] Gout is a metabolic disorder that is the most common manifestation of hyperuricemia. In this case, the patient's gout was diagnosed 5 years ago, which is a conceivable risk factor and the cause of repeated episodes of hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Experimental studies have also confirmed the role of urate in animal models of AKI. [5,10] The pathogenesis of AKI caused by hyperuricemia involves both crystal-independent and crystal-dependent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations